2007
DOI: 10.1016/j.ejvs.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Dysfunction in Patients Older than 54 Years of Age with Objective Evidence of Arteriosclerosis

Abstract: In subjects older than 54, NMD measured at 3 or 4 minutes after NTG administration would underestimate the NTG-dependent vasodilatation. NMD measured with the maximal responded diameter was associated with atherosclerotic risk factors, and it is therefore considered to be an important parameter in patients with atherosclerotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…NMD3 is suggested to underestimate the extent of vasodilatation induced by the sublingual application of NTG; however, NMD3 was able to predict cardiovascular events in the current study. Our previous report suggested that NMD was associated with atherosclerotic risk factors, but that NMD3 displayed no such association 19) . NMD displays the dilative potency of NTG, while NMD3 provides a measure of the speed of response to NTG, or provides a limited measure of dilatation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NMD3 is suggested to underestimate the extent of vasodilatation induced by the sublingual application of NTG; however, NMD3 was able to predict cardiovascular events in the current study. Our previous report suggested that NMD was associated with atherosclerotic risk factors, but that NMD3 displayed no such association 19) . NMD displays the dilative potency of NTG, while NMD3 provides a measure of the speed of response to NTG, or provides a limited measure of dilatation.…”
Section: Discussionmentioning
confidence: 96%
“…The power of brachial NMD to be used as a clinical marker of cardiovascular disease is unclear. Our previous study showed that brachial responses to NTG reached a maximal limit approximately 7 minutes after the administration, and that NMD correlated with atherosclerotic risk factors in patients displaying evidence of atherosclerosis 19) . The current study was undertaken to investigate whether NMD can provide prognostic information on cardiovascular disease.…”
Section: Introductionmentioning
confidence: 90%
“…Because of ethical concerns in a predominantly healthy cohort, we did not administer the medication glyceryl trinitrate to assess nitroglycerinmediated dilation, which provides additional information on the maximum, nonendothelium-dependent vasoreactivity and pulse waveform changes. [33][34][35] We only measured vascular function once in every individual, which does not account for intraindividual variability and circadian rhythms. In addition, recent studies suggest that the maximal increase in diameter occurs Ͼ60 seconds after cuff release.…”
Section: Limitationsmentioning
confidence: 99%
“…Impaired FMD has been reported in patients with PAD and IC. [13][14][15][16] However, whether vascular reactivity is related to the severity of the disease in patients with IC remains unclear. Moreover, there is scarce information regarding the relationship between functional decline and vascular reactivity.…”
Section: Introductionmentioning
confidence: 99%